Teaching Chemistry in Context: Its Effects on Students’ Motivation, Attitudes and Achievement in Chemistry - Magwilang, Epiphania B. (International Journal of Learning, Teaching and Educational Research, 2016)
Context-based approach in chemistry teaching presents scientific concepts by establishing contexts and relationships selected from daily life events. It has come into wide use recently with the aim of bridging the gap between students’ daily life experiences and the content of the chemistry course. It is along this line that the researcher motivated to evaluate the effectiveness of context-based teaching approach towards students learning, their motivation to learn chemistry, their attitudes towards chemistry lessons and their level of success in understanding the concepts that were taught. The study made use of an experimental research method with pretest-posttest control group design involving 96 students from two inorganic chemistry classes in at the State Polytechnic College of Mountain Province, Philippines. The Context-based Chemistry Motivation Scale, the Attitude toward Chemistry Lessons Scale and achievement tests were used as data gathering instruments. The score averages and standard deviations of score distributions were calculated while t-test was used for group comparisons. Results indicated that students in the treatment group demonstrated significantly higher motivation levels, attitude levels and academic achievement as compared to the control group. Thus, the study concluded that context-based learning improved students’ motivation in learning chemistry and their attitude towards the chemistry course as well as increased their achievement levels in the subject.